Crystal structure of (dibenzyl sulphoxide-κO)bis(2-chlorobenzyl-κC1)dichloridotin(IV), C28H26Cl4OSSn - Lee, See Mun *; Lo, Kong Mun *; Tiekink, Edward R. T. * (de Gruyter, 2019)
C28H26Cl4OSSn, monoclinic, P21/c (no. 14), a = 10.6342(2) Å, b = 12.9298(3) Å, c = 20.3576(4) Å, β = 101.820(1)°, V = 2739.78(10) Å3, Z = 4, Rgt(F) = 0.0197, wRref(F2) = 0.0520,T = 100(2) K.